Sociolinguistic perspectives on everyday digital practices - Barton, David; Lee, Carmen; Jones, Rodney; Vasquez, Camilla (AoIR Selected Papers of Internet Research, 2016)
The four papers in this panel are by linguists who share a common approach to the study of language combining discourse studies and ethnographic approaches to the analysis of people’s experiences of online life. The first paper is an examination of academics’ changing writing practices and likes and hates in relation to technology in their work lives and everyday lives. It is based on detailed observation and repeated in-depth techno-biographic interviews about their changing writing practices. The paper explores in depth 2 examples of digital writing practices, emailing and using PowerPoint, and it draws on the sociolinguistic concept of ‘stance-taking’ to make sense of these changing practices. It documents how everyday devices and practices get adapted in the workplace and how the boundaries between home and work are eroded. This leads to tensions and conflicts between enhanced academic freedom and greater managerial control. The second study also draws upon the concept of affect, but in a very different context. It investigates affective hashtags about a protest movement in terms of: the linguistic codes used to create hashtags; what gets done by posting hashtags; and hashtags as a resource for self-positioning and identity claims. Hashtags have been taken up widely in political movements in that they connect people easily by being hyperlinked and searchable. The study takes an event-based approach to data collection, focusing on the Hong Kong “Umbrella Movement”. Over 9,000 Instagram hashtags from 700 posts with the Chinese hashtag for umbrella movement were retrieved over a 4 month period. This was complemented by online interviews with selected Instagram users. Three stages of data analysis involved: understanding hashtags as speech acts; examining language choice and displays of affect; and how affective hashtags are used to perform identities. Overall, the study rethinks the relations between language and emotion, between language and social actions, and crucially, between online and offline, arguing that multilingual hashtags are a powerful linguistic resource for authentication of identities. The third paper examines people’s experience and positioning in relation to online surveillance as a social and discursive practice. It is based on a year long ethnographic study involving university students from Britain, China and Hong Kong, in order to understand the experience of digital surveillance from the perspective of users of technologies. The paper begins by documenting the spread of new forms of surveillance in social networking sites, search engines and mobile apps. Sharing information about themselves and gathering information about others has become an integral part of online life. This paper argues that linguistic issues are central: issues about how people manage identities and activities in social interaction with language, and issues about how they discursively negotiate participation roles in discourse. Drawing on concepts from mediated discourse analysis, interactional sociolinguistics, and new literacy studies it describes how practices of surveillance are mediated through discursive resources. It explores digital surveillance as a form of ‘literacy’, arguing that being able to manage online privacy requires being able to read and write in particular ways, to pragmatically manage particular kinds of interactions, and to construct particular kinds of social identities. Building on earlier literature about online reviews, the last paper is concerned with parodies of online consumer reviews. It considers how review sites can serve as a space for creative contestation and playful resistance and shows the various ways in which users re-imagine and re-purpose the review space, as a site for entertainment and activism. It focuses primarily on parody reviews found on Amazon. Previous analysis of 1000 reviews has identified a set of core discourse practices that appear across all sites; these include evaluation, identity claims and narrativity. By intertextually drawing on, and creatively re-appropriating, recognizable features of bona fide reviews, authors of review parodies demonstrate their knowledge of the very genre they are imitating. The most obvious characteristic of online review parodies is how they take the form of “mock narratives,” as authors enlist a range of discursive resources to perform particular identities and to create imagined stories. The paper argues that although many of these playful texts appear to be subverting the primary consumerist goal-orientation of the review site, their meanings ultimately remain ambivalent. It further explore how other users react to parodies, highlighting users’ various understandings of the tacit rules underlying what content is appropriate for the review space. Each paper in this panel demonstrates the value of detailed analysis of language to reveal more about how the online world works, including users’ perspectives. These are all research sites where there are relationships of unequal power alongside tensions and disagreements. Themes cutting across all 4 papers include: the interweaving of online and offline practices; the making and breaking of rules; affect, emotion and evaluation; and the constructions of digital identities.